A Case Study: Miniso - Jigyasa Jayant; Kunal Malhotra; Mariam Adnan Alanjeri; Ishlok Mittal (AIBPM Publisher, 2020)
MINISO was founded in 2011 by Chinese entrepreneur Ye Guo Fu and Japanese designer Miyake Junya. Initially claiming to be a famous Japanese brand, despite operating in china. In such short period, this company has detonated as an emerging business empire with 1,800 stores in 40 countries, delivering an heterogenous collection of affordable, curated goods, challenging the physical pessimists. MINISO is now emerging as one of the top market brands. MINISO tag line isâ€“ â€œlet consumers around the world buy better quality products at lower pricesâ€. At the time of establishment of MINISO, the physical economy was in decline due to the rise of e-commerce. Physical economy had applied a monopolistic influence on the market depend on its sales channel advantage. Even though MINISO was a success by providing the actual value of the products, and focuses on quality improvements. MINISO estimate to open 6000 stores worldwide. The purpose of this study is to present a reality check to the power of physical retailer in the rise of the digital marketing. MINISO is brick-and-mortar-only business model built around the reality of a world with e-commerce. Over careful consideration of the customer and a unique artistic product, it achieves to do what online stores cannot: deliver an experience.